2013
DOI: 10.5958/j.2249-6270.3.3.038
|View full text |Cite
|
Sign up to set email alerts
|

An Economic Analysis of Intraclass Marriage

Abstract: This paper investigates mate selection behavior with respect to both class position and individuals characteristics in the marriage market. The theoretical prediction of model can suggest not only those ones that belong to upper and lower class will marry within own class but also they can form the interclass marriage. Accordingly, the hypothesis is that the persons in upper and lower classes marry within own class. Logit regressions show that the ratio of probability of intraclass to interclass marriage decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The criteria for spouse selection can be either intrinsic (physical attractiveness) or extrinsic (being intelligent) (5). The theory of homogamy postulates that like attracts like, and every individual usually selects someone who is most similar to them concerning age, religion, nationality, and education (6,7). Some research has reported that despite changes in the rules for marriage with people of color over time, white women still tend to marry their peers (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…The criteria for spouse selection can be either intrinsic (physical attractiveness) or extrinsic (being intelligent) (5). The theory of homogamy postulates that like attracts like, and every individual usually selects someone who is most similar to them concerning age, religion, nationality, and education (6,7). Some research has reported that despite changes in the rules for marriage with people of color over time, white women still tend to marry their peers (8,9).…”
Section: Introductionmentioning
confidence: 99%